2.5D peritumoural radiomics predicts postoperative recurrence in stage I lung adenocarcinoma - Lan, Haimei; Wei, Chaosheng; Xu, Fengming; Yang, Eqing; Lu, Dayu; Feng, Qing; Li, Tao (Frontiers in Oncology, 2024)
Objective：Radiomics can non-invasively predict the prognosis of a tumour by applying advanced imaging feature algorithms.The aim of this study was to predict the chance of postoperative recurrence by modelling tumour radiomics and peritumour radiomics and clinical features in patients with stage Ⅰ lung adenocarcinoma(LUAD). Materials and methods：Retrospective analysis of 190 patients with postoperative pathologically confirmed stage Ⅰ LUAD from centre 1, who were divided into training cohort and internal validation cohort, with centre 2 added as external validation cohort. To develop a combined radiation-clinical omics model nomogram incorporating clinical features based on images from low-dose lung cancer screening CT plain for predicting postoperative recurrence and to evaluate the performance of the nomogram in the training cohort, internal validation cohort and external validation cohort. Results：A total of 190 patients were included in the model in centre 1 and randomised into a training cohort of 133 and an internal validation cohort of 57 in a ratio of 7:3, and 39 were included in centre 2 as an external validation cohort. In the training cohort (AUC=0.865, 95% CI 0.824-0.906), internal validation cohort (AUC=0.902, 95% CI 0.851-0.953) and external validation cohort (AUC=0.830,95% CI 0.751-0.908), the combined radiation-clinical omics model had a good predictive ability. The combined model performed significantly better than the conventional single-modality models (clinical model, radiomic model), and the calibration curve and decision curve analysis(DCA) showed high accuracy and clinical utility of the nomogram. Conclusion：The combined preoperative radiation-clinical omics model provides good predictive value for postoperative recurrence in stage ⅠLUAD and combines the model's superiority in both internal and external validation cohorts, demonstrating its potential to aid in postoperative treatment strategies.